Relationship of Parents' Socio-Economic Status to Student Achievement - Arif Zaenal Arifin; Friska Rahmatika Azizah; Mutiara Putri; Nur Afiah; Rohanah Rohanah; Rosaninda Rosaninda; Iis Holiah (PT. Pusmedia Group Indonesia, 2023)
The economic well-being of parents can affect all aspects of life in the family, including by affecting the learning process of a child or student. This study aims to determine the condition of the socioeconomic status of students' parents, the learning achievement of high-class students and to determine the relationship between parents' socioeconomic status and student learning achievement. The method used in this study is descriptive qualitative. The subjects in this study were students who were ranked from 1 to 5 in high grades, namely class IV and V MI Al Washliyah perbutulan Cirebon. Data collection techniques that researchers use are by using observation and direct interviews. The data analysis technique used in this study is a qualitative descriptive method that is by looking for, collect, and organize systematically. Based on the results of research on the relationship between parents' socioeconomic status and learning achievement in high-class students at MI Al Washliyah, it can be concluded that there is a positive relationship between parents' socioeconomic status and learning achievement. From the explanation above, it can be seen that the socioeconomic status of parents has a significant positive relationship with student learning achievement. This shows that the higher the socioeconomic status of the parents, the higher the learning achievement of the learners. vice versa, the lower the socioeconomic status of parents, the lower the impact on student learning achievement